Increased somatic mutation burdens in normal human cells due to defective DNA polymerases - Robinson, Philip S.; Coorens, Tim H. H.; Palles, Claire; Mitchell, Emily; Abascal, Federico; Olafsson, Sigurgeir; Lee, Bernard C. H.; Lawson, Andrew R. J.; Lee-Six, Henry; Moore, Luiza; Sanders, Mathijs A.; Hewinson, James; et al. (Nature genetics, 2021)
Mutation accumulation in somatic cells contributes to cancer development and is proposed as a cause of aging. DNA polymerases Pol ε and Pol δ replicate DNA during cell division. However, in some cancers, defective proofreading due to acquired POLE / POLD1 exonuclease domain mutations causes markedly elevated somatic mutation burdens with distinctive mutational signatures. Germline POLE / POLD1 mutations cause familial cancer predisposition. Here, we sequenced normal tissue and tumor DNA from individuals with germline POLE / POLD1 mutations. Increased mutation burdens with characteristic mutational signatures were found in normal adult somatic cell types, during early embryogenesis and in sperm. Thus human physiology can tolerate ubiquitously elevated mutation burdens. Except for increased cancer risk, individuals with germline POLE / POLD1 mutations do not exhibit overt features of premature aging. These results do not support a model in which all features of aging are attributable to widespread cell malfunction directly resulting from somatic mutation burdens accrued during life. Healthy tissues from individuals with germline mutations in POLE or POLD1 show increased mutational burden, suggesting that normal cells are capable of tolerating high mutation rates.